Clinical Characterization According to Age Group of Patients with Rheumatoid Arthritis - Neima Ayde Bravo Mego; María Lucelita Silva Coronel; José Ander Asenjo Alarcón (Revista Finlay)
Foundation: rheumatoid arthritis affects the quality of life of patients due to the functional alterations it causes; identifying the clinical manifestations according to their particularities will favor diversified and personalized action. Objective: to determine the clinical characteristics according to age group of patients with rheumatoid arthritis treated in a primary hospital in Peru. Methods: a descriptive, retrospective and cross-sectional study was carried out between August and September 2023, with 50 patients enrolled at the Chota Hospital, Peru. The data were obtained with a revised and adapted collection form. The statistical analysis includes absolute and relative frequencies, 95 % confidence intervals, Chi square for homogeneity and Fisher's exact test with p < 0.05 for significance. Results: 82.8 % of adults and 81.0 % of older adults presented polyarticular pain; subcutaneous nodules 24.1 % and 19.0 %; morning stiffness 24.1 % and 9.5 %; joint deformity 20.7 % and 9.5 % and joint numbness 10.3 % and 19.0 % of adults and older adults; 96.6 % of adults and 90.5 % of older adults had positive rheumatoid factor and elevated C-reactive protein; 53.6 % and 47.6 % respectively. The clinical and laboratory differences according to age group were not significant (p > 0.05). Conclusion: polyarticular pain was the most frequent manifestation, with positive rheumatoid factor and elevated C-reactive protein, both in adults and older adults. Individualized support will contribute to a more specific assessment of patients, in order to establish adapted control and support measures.